Potential production of carbon nanotubes from liquid aromatic hydrocarbons over Fe and Ni on alumina powder via catalytic chemical vapor deposition - San M.T. (2023)
In this study, liquid aromatic hydrocarbons of benzene C6H6, toluene C7H8, and xylene C8H10 (BTX), which can be abundantly found in industrial waste oil and pyrolysis products of waste plastics, were used as carbon sources to produce carbon nanotubes (CNTs). CNTs were firstly synthesized from liquid benzene over powdered alumina (Al2O3) supported Fe and Ni catalysts at 700 to 850 °C via catalytic chemical vapor deposition (CCVD) method. It was found that, CNTs synthesized from Fe/Al2O3 resulted in significantly higher carbon yields at 1.0–5.6 wt% with relatively higher graphitization analyzed by Raman spectroscopy compared to those of Ni/Al2O3 with the yields only at 0.6–2.8 wt%. However, smaller sizes of CNTs at 20–29 nm could be produced from Ni/Al2O3 compared to 30–38 nm obtained from Fe/Al2O3 due to its smaller crystallite size of the initial catalyst confirmed by X-ray diffraction (XRD) analysis. For both catalysts, with increasing CCVD temperature, the yields tended to increase with a slight increase in CNT diameter and graphitization degree. The temperature of 800 °C was then chosen for further preliminary investigation on potential mass production of CNTs from BTX. By doubling the amount of catalysts, the CNT yield could be approximately twice achieved by maintaining its uniformity and quality because of remaining active sites of the catalysts. In addition, increasing the carbon atoms of aromatic hydrocarbons resulted in improved yields without changing the quality of CNTs. Finally, kinetic mechanisms of CNT growth from BTX decomposition using Fe/Al2O3 catalyst were simply investigated by varying reaction time from 10 to 60 min. At feeding flow of 0.5 mL/min, optimum reaction time was achieved at 30 min in order to produce uniform CNTs at high yields without carbon loss, unreacted BTX, and undesired by-products, which possibly occurred by hydrogenation, catalyst deactivation, and/or side reactions of as-produced gaseous hydrocarbons during CCVD reaction.